Sugar-sweetened beverages and the risk of hyperuricemia and gout: a meta-analysis - Lu, Yuejie; Wang, Yinuo; Huang, Renjie; Pan, Hejing; Xie, Zhijun; Wen, Chengping; Huang, Lin; Li, Xuanlin (Frontiers in Nutrition, 2025)
ObjectiveThis meta-analysis aimed to investigate the association between sugar-sweetened beverages (SSBs), fructose, and the risk of gout and hyperuricemia.MethodsFollowing PRISMA guidelines, we systematically searched PubMed, EMBASE, and Cochrane Library for observational studies from inception to March 2025. Adjusted odds ratios (ORs) with 95% confidence intervals (CIs) were pooled using random/fixed-effects models. Subgroup analyses explored sex. Heterogeneity (I2) and publication bias were assessed.ResultsA total of 22 studies (235,790 participants) were included. SSB intake significantly increased the risk of hyperuricemia (OR = 1.33, 95% CI: 1.23–1.44) and gout (OR = 1.21; 95% CI 1.11–1.32). Fruit juice (FJ) showed a modest association with hyperuricemia (OR = 1.15, 95% CI: 1.02–1.29) and an increased risk of gout (OR = 1.28; 95% CI 0.96–1.72). Fructose consumption was strongly associated with increased gout risk (OR = 1.66, 95% CI: 1.27–2.18), but its relationship with hyperuricemia was inconsistent (OR = 1.12, 95% CI: 0.85–1.46). DSD showed a modest association with gout (OR = 1.14; 95% CI 0.95–1.35). Subgroup analysis revealed SSB and FJ consumption associated with elevated risks of hyperuricemia in males (SSBs: 1.37; FJ: 1.15) compared to females (SSBs: 1.29; FJ: 1.13).ConclusionsSSB consumption is associated with increased risks of hyperuricemia and gout, particularly in males.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=1040227, PROSPERO (Unique Identifier: CRD420251040227).